Gibraltar Neanderthals and results of recent excavations in Gorham's, Vanguard and Ibex Caves - Barton, R; Currant, A; Fernandez-Jalvo, Y; Finlayson, J; Goldberg, P; Macphail, R; Pettitt, P; Stringer, C (1999)
While the sites of Forbes' Quarry and Devil's Tower are, respectively, unpromising and probably too dangerous for further excavation, there are several other sites on the Rock preserving evidence of Neanderthal activities. One, Ibex Cave, lies high up on the eastern face of the Rock, while four others lie to the southeast, close to the sea near 'Governor's Beach'. The present beach mainly consists of fine limestone blast debris from military tunnelling operations, but there are also cemented remnants of more ancient beaches which presumably accumulated during Oxygen Isotope Stage 5. The caves are named (from the south) Bennett's, Gorham's, Vanguard and Boat Hoist. Three of these caves (Ibex, Gorham's and Vanguard) have been excavated since 1994 as part of the Gibraltar Caves Project; some of the initial results of this work are presented below. Further details will appear in the proceedings of the Gibraltar conference held in August to celebrate the 150th anniversary of the finding of the Forbes' Quarry skull (Stringer et al. in preparation). The excavations at Gorham's and Vanguard Caves are already beginning to yield significant results relating to the palaeontological, archaeological and palaeoenvironmental aspects of the Neanderthals and their modern human successors. The integration of new AMS and other dating results with sediments analysis should help us compare the sequences in both caves and to provide frameworks for situating human behaviour. For example, it would be interesting to know whether changes in sea level and resulting reconfiguration of the coastal plain were major factors responsbile in the Neanderthal exploitation of highly local raw materials for tool-making and the frequency of gathering of marine/estuarine foods. Using this information and comparing the archaeological evidence from the Middle and Upper Palaeolithic levels at the sites will help to place the Gibraltar finds in their European and Mediterranean contexts.